Transaksi Keuangan E-Wallet Ditinjau Dari Perspektif Hukum Islam - Fitriyani, Putri; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2025)
Currently, saving in e-wallet applications is more popular with the public than saving in regular wallets. In addition to making transactions easier, there are many features provided by e-wallet application developers that can be used by users. These features often include payment services, bill payments, fund transfers, and other financial services, making it more convenient for users to manage their finances. However, with the increasing number of these features, open questions arise about the permissibility of transactions made through e-wallet applications and whether they align with sharia principles. The aim of this study is to discuss how financial transaction components work through digital wallets and how Islamic law regulates financial transaction instruments using digital wallets. The data collection method used in this research involves examining and analyzing books, articles, journal papers, notes, and reports that are relevant to the issues discussed. From the results of research from various sources, the author concludes that there are several financial transaction instruments through digital wallets that are carried out under various contracts such as sale and purchase contracts, ijarah contracts, and wadi'ah contracts. According to Islamic law, the currency exchange mechanism using digital wallets is permissible as long as it meets sharia standards and is free from elements such as usury, uncertainty (gharar), and gambling (maysir). This is because e-wallets serve as a secure money storage tool, where the value of the money stored corresponds to the amount stated in the e-wallet, ensuring that transactions remain within the boundaries of Islamic financial principles.